Single cell studies on the role of B-cell stimulatory factor 1 in B-cell activation. - Alderson, M R (1987)
The role of the T-cell-derived lymphokine B-cell stimulatory factor 1 (BSF-1) in the early activation, proliferation, and antibody-forming cell (AFC) clone formation of single fluorescein-specific B lymphocytes isolated from normal mouse spleens by hapten-gelatin adherence has been studied in vitro. BSF-1 acting alone induced early B-cell activation, as assessed by a significant increase in cell diameter of single B cells cultured for 24 hr. A small but significant number of these B cells formed proliferating clones, some of which secreted antibody. When acting with the specific antigen fluorescein-polymerized flagellin, BSF-1 augmented early cell enlargement and markedly enhanced proliferation, but it did not increase the frequency of AFC clones stimulated by fluorescein-polymerized flagellin alone. The further addition of recombinant murine interleukin 1 (IL-1) marginally enhanced proliferation caused by antigen plus BSF-1. No synergy was observed between BSF-1 and IL-1 for antibody formation. In the presence of fibroblast filler cells, BSF-1 substantially inhibited AFC clone development achieved by antigen plus IL-1. BSF-1 was also found to be inhibitory to AFC clone development stimulated by specific antigen acting with either recombinant human interleukin 2 (IL-2) or with IL-2 plus IL-1, both in the presence or absence of filler cells. The results suggest that BSF-1 plays a complex role in the regulation of the B-cell activation pathway by enhancing early activation and antigen-specific proliferation as well as inhibiting the effects of other B-cell factors on antibody formation. BSF-1 is the only cytokine so far tested in the single B-cell system that acts with antigen to promote proliferation without concomitant antibody production.